Constructive Possession in the Sale and Purchase of Gold According to Changes in the Customary Practice - Yahaya, Mohammad Zaini (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
In a sales and purchase transaction, gold is a ribawī item that requires taking possession (qabḍ) of goods on a spot basis. Since the al-Qur’an and al-Sunnah have not specifically mentioned the form of qabḍ in a sales and purchase transaction, the ulama has made customary practice (‘urf) as a reference when determining whether a card is appropriate or otherwise. Besides that, the ulama has also accepted constructive possession (qabḍ ḥukmī) as a substitute for physical possession (qabḍ ḥaqīqī) in a sales and purchase transaction. The purpose of this study is to examine the validity of qabḍ, the forms of qabḍ, the classification of qabḍ ḥukmī in buying and selling gold, and the application of 'urf as a reference in the validity of qabḍ. The study is a normative legal study using uṣūl al-fiqh and fiqh al-mu'āmalāt analysis tools. The results of the study show that rapid technological developments have changed some forms of buying and selling transactions, including those involving gold. The main challenge in transactions involving gold is the issue of qabḍ, especially those that do not involve physical gold. This is due to certain constraints, especially buying and selling online. Based on the views of the scholars in determining the forms of qabḍ ḥukmī to see the suitability of gold buying and selling applications at this time, this kind of buying and selling is permissible. As long as there is takhliyyah and tamkin in the gold being traded, then it may be accepted as qabḍ ḥukmī. In addition, it must be ensured that the allocation steps, such as tagging of the physical gold, are implemented on the day of the contract to avoid ribā al-nasī’ah.